Experiences of moral distress in a COVID‐19 intensive care unit: A qualitative study of nurses and respiratory therapists in the United States. Issue 1 (17th June 2022) - Trachtenberg, Sophie; Tehan, Tara; Shostak, Sara; Snydeman, Colleen; Lewis, Mariah; Romain, Frederic; Cadge, Wendy; McAuley, Mary Elizabeth; Matthews, Cristina; Lux, Laura; Kacmarek, Robert; Grone, Katelyn; et al.
Abstract: The COVID‐19 pandemic has placed extraordinary stress on frontline healthcare providers as they encounter significant challenges and risks while caring for patients at the bedside. This study used qualitative research methods to explore nurses and respiratory therapists' experiences providing direct care to COVID‐19 patients during the first surge of the pandemic at a large academic medical center in the Northeastern United States. The purpose of this study was to explore their experiences as related to changes in staffing models and to consider needs for additional support. Twenty semi‐structured interviews were conducted with sixteen nurses and four respiratory therapists via Zoom or by telephone. Interviews were transcribed verbatim, identifiers were removed, and data was coded and analyzed thematically. Five major themes characterize providers' experiences: a fear of the unknown, concerns about infection, perceived professional unpreparedness, isolation and alienation, and inescapable stress and distress. This manuscript analyzes the relationship between these themes and the concept of moral distress and finds that some, but not all, of the challenges that providers faced during this time align with previous definitions of the concept. This points to the possibility of broadening the conceptual parameters of moral distress to account for providers' experiences of treating patients with novel illnesses while encountering institutional and clinical challenges.